2016
DOI: 10.12659/msm.896869
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implants in Subjects Over Age 65: Quality of Life and Audiological Outcomes

Abstract: BackgroundCochlear implants (CIs) have been recognized as a safe and effective means for profound hearing loss rehabilitation in children and adults and recently their use has been extended to subjects over 65 years of age. The aim of this paper was to assess indices related to changes in the quality of life (QoL) in elderly CI recipients.Material/MethodsA case-control paradigm was used to assess the effects of CIs on the QoL. Forty-two subjects were assigned to the Case group and 15 subjects to the Control gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
3
23
2
4
Order By: Relevance
“…Values obtained in the GBI also indicated that an overall benefit had been provided by the implant: The mean GBI total score was 28 ± 6, with significant gains in the general health subscale, but no improvement in the physical and social subscales. These scores were in line with the GBI scores reported for cochlear implantation in other studies (Aimoni et al, 2016;Guerra-Jimenez et al, 2016;Lassalette et al, 2015;Sanchez-Cuadrado et al, 2015). These objective and subjective improvements are interesting to note in the context of a study group where subjects had considerable hearing in the contralateral ear, with the upper quartile for preoperative speech scores in the best-aided condition >50% for monosyllabic words, and >60% for sentences in noise.…”
Section: Discussionsupporting
confidence: 88%
“…Values obtained in the GBI also indicated that an overall benefit had been provided by the implant: The mean GBI total score was 28 ± 6, with significant gains in the general health subscale, but no improvement in the physical and social subscales. These scores were in line with the GBI scores reported for cochlear implantation in other studies (Aimoni et al, 2016;Guerra-Jimenez et al, 2016;Lassalette et al, 2015;Sanchez-Cuadrado et al, 2015). These objective and subjective improvements are interesting to note in the context of a study group where subjects had considerable hearing in the contralateral ear, with the upper quartile for preoperative speech scores in the best-aided condition >50% for monosyllabic words, and >60% for sentences in noise.…”
Section: Discussionsupporting
confidence: 88%
“…A cochlear implant is an alternative electronic device that is used in profound hearing loss when a conventional amplification hearing aid had little or no benefit or cannot be used. Aimoni et al [ 12 ] conducted a case–control paradigm to assess whether cochlear implants influenced quality of life in 57 participants aged over 65. 42 participants were assigned to the case group and 15 a control group.…”
Section: Resultsmentioning
confidence: 99%
“…Audiological data and Quality of Life data via the glasgow benefit inventory (GBI) was collected on four occasions: 1 month before implantation; 1 day pre-implantation; 30 days post-implantation; 12 months post-implantation. Their results showed significant improvements in post implant scores in both their audiological tests and quality of life [ 12 ]. Hilly et al [ 13 ] researched into a very similar area in their retrospective chart review of cochlear implants.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the included articles, 68 did not meet the inclusion criteria listed above and were excluded for the following reasons. Twenty-two studies only measured HRQoL after implantation, but not before [Kelsall et al, 1995;Shin et al, 1997;Kunimoto et al, 1999;Eshraghi et al, 2009;Ramos et al, 2013;Sanchez-Cuadrado et al, 2013;Cloutier et al, 2014;Huarte et al, 2015;Sladen and Zappler, 2015;Speers et al, 2015;Aimoni et al, 2016;Alhanbali et al, 2016;Manrique-Huarte et al, 2016;Ramos-Macias et al, 2016;Hinder et al, 2017]. They were excluded because only studies assessing changes in HRQoL were accepted for review.…”
Section: Study Selectionmentioning
confidence: 99%